Modeling of single mode optical waveguide using finite different method (FDM) / Nor Rosmiza Ab Latif - Ab Latif, Nor Rosmiza (2014)
This project is about numerical analysis of optical waveguide to analyze the propagation constant of the waveguides and obtain the TE field distributions. Numerical technique is essential in optical waveguide because they are easier to use and more transparent. To model the single mode optical waveguide structure, we have used Finite Different approach as one of the waveguide to simulate the electric field distribution. The waveguide allows guided wave propagation only if the thickness is greater than a critical cutoff thickness for each waveguide mode. From that, electric field distribution of 1550nm and 1310nm can be acquired and analysed. The waveguide structure of 1550nm shows better electric field distribution compared to 1310nm wavelength since the 1550nm waveguide can maximize the bandwidth system with low attenuating loss.